2019
DOI: 10.1007/s00345-018-02623-4
|View full text |Cite
|
Sign up to set email alerts
|

Patients knowledge and experience with urinary and peripheral intravenous catheters

Abstract: Purpose Inappropriate use of urinary and intravenous catheters is still frequent. The use of catheters is associated with some serious complications, such as health care associated infections (HAIs). An efficient way to reduce HAIs is to avoid inappropriate use of catheters, but the role for patients in quality improvement initiatives is unclear. The aim of this study is to investigate patients knowledge and experience with catheters, to design patient interventions to reduce inappropriate catheter use. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Lo et al, ; Loveday et al, ). Studies have shown that around 20% of patients in hospital may not know the indication for their IDC (Darbyshire, Rowbotham, Grayson, Taylor, & Shackley, ; Laan, Nieuwkerk, & Geerlings, ), which was similar to the rate found in the initial practice adherence audits in the present study. In the present study, patient understanding of IDC indication improved significantly during the intervention period, from 78%–89%, with the implication being that improved patient education empowers patients to ask clinicians about the continued need for their IDC, potentially leading to earlier removal of IDC and reduced CAUTI risk.…”
Section: Discussionsupporting
confidence: 88%
“…Lo et al, ; Loveday et al, ). Studies have shown that around 20% of patients in hospital may not know the indication for their IDC (Darbyshire, Rowbotham, Grayson, Taylor, & Shackley, ; Laan, Nieuwkerk, & Geerlings, ), which was similar to the rate found in the initial practice adherence audits in the present study. In the present study, patient understanding of IDC indication improved significantly during the intervention period, from 78%–89%, with the implication being that improved patient education empowers patients to ask clinicians about the continued need for their IDC, potentially leading to earlier removal of IDC and reduced CAUTI risk.…”
Section: Discussionsupporting
confidence: 88%
“…The details of these studies are presented in table 1. Patients say using urinary catheter feel embarrassed, discomfort, painful, unfree, blocking their movement (Darbyshire et al, 2016;Laan et al, 2019;Trautner et al, 2019). This in supported by research from Safdar et al, (2016).…”
Section: B Patient's Experiencementioning
confidence: 93%
“…Two articles discuss how the patient's experiences based on the type of urinary catheter and patient's reason using catheter. The result show the patient's reason using urinary catheter are urinary retention, post stroke or trauma, incontinence, and post urology surgery (Darbyshire et al, 2016;Laan et al, 2019).…”
Section: B Patient's Experiencementioning
confidence: 98%
“…Several projects are described in more detail in other papers. [14][15][16][17][18][19][20][21][22][23]…”
Section: The Projects' Structurementioning
confidence: 99%